Euro-Par 2015 : parallel processing : 21st International Conference on Parallel and Distributed Computing, Vienna, Austria, August 24-28, 2015, Proceedings /: parallel processing : 21st International Conference on Parallel and Distributed Computing, Vienna, Austria, August 24-28, 2015, Proceedings. (2015) - Unknown
No abstract available